Development and Validation of HPLC-UV Method for the Determination of a Potent Synthetic Cannabinoid THJ-2201 in Mouse Plasma and Application in a Pharmacokinetic Study - Aboul-Enein, Hassan Y.; Mostafa, Gamal A.E; AlRabiah, Haitham; Al-Ramadi, Mohammed; Attia, Sabry M.; Wagdy, Hebatallah A. (Current Pharmaceutical Analysis, 2020)
Aim: A new simple and sensitive high-Performance Liquid Chromatography (HPLC) method for the determination of a potent synthetic cannabinoid THJ-2201, has been developed and validated. Lixiviptan was used as the Internal Standard (IS). Methods: THJ-2201 and IS were extracted from mouse plasma using deproteinization procedure that uses acetonitrile followed by HPLC analysis. The separation was carried out on a reversed-phase C18 column using water and acetonitrile mixture (30:70 v/v). The flow-rate was 1.0 mL/min. Eluting of both THJ-2201 and lixivaptan was performed at 220 nm. Results: The method demonstrated linearity over a calibration range of 95 - 1500 ng/mL and the Limit of Detection (LOD) and Quantitation (LOQ) were 28 ng/mL and 91 ng/mL, respectively. The validation of the proposed method was carried out by following the US Food and Drug Administration (FDA) guidelines. Intra- and inter-day precision did not exceed 6.4%, whereas the accuracy of THJ-2201 measurements was within ±13%. Conclusion: This new method is simple and sensitive and has been applied successfully in a pharmacokinetic study of THJ-2201 in mouse plasma. The mean values of Tmax and Cmax were 0.25 h and 141.87 ± 12.11 ng/mL, respectively.
Keywords: THJ-2201